7번 염색체 장완 미세결실 환아에서 나타난 안과적 이상 2예 - 김상윤(Sang Yoon Kim); 이승민(Seung Min Lee); 신종훈(Jonghoon Shin); 이지은(Ji Eun Lee); 김수진(Su Jin Kim) (Daihan angwa haghoi jabji, 2021)
목적: 7q 염색체 미세결실 환아에서 나타난 안과적 증상 2예를 보고하고자 한다. 증례요약: (증례 1) 생후 64일 남자 환아가 DNA 미세배열 비교유전자보합법과 형광제자리부합법에서 7번 염색체의 미세결실(7q36.2q36.3 deletion)이 발견되어 안과적 평가를 위해 내원하였다. 안저검사에서 양안 시신경유두 저형성, 우안 망막출혈을 동반한미숙아망막병증이 관찰되었다. 생후 24개월경에는 간헐외사시 및 양안의 굴절부등이 발견되어 안경착용을 시작하였다. (증례 2) 만 3세의 남아가 뇌성마비 및 발달지연으로 재활치료하던 중 눈의 초점이 잘 맞지 않는 증상이 발견되어 안과로 의뢰되었다. 안저검사 결과 양안 시신경유두함몰비가 증가되어 있었고, 섬광 시유발전위검사에서 양안 p100 지연 소견을 보였으며, 원거리 40프리즘디옵터의 외사시가 관찰되었다. DNA 검사에서 환아의 7번 염색체 장완의 미세결실(7q35 microdeletion) 및 CNTNAP2 유전자 소실이 확인되었다. 결론: 안구발달에 관여하는 유전자 이상이 발견되는 경우, 안과적 이상을 조기에 발견하고 적절한 치료를 함으로써 정상적인 시기능 발달이 가능하도록 해야 할 것이다. Purpose: We report ocular manifestations in two patients with 7q microdeletion. Case summary: (Case 1) A 62-day-old male infant was admitted to the ophthalmology outpatient department for ocular examination after being diagnosed with microdeletion of chromosome seven (7q36.2q36.3 deletion) in DNA microarray comparative genomic hybridization (DNA microarray CGH) and fluorescence in situ hybridization (FISH) tests. Fundus examination showed optic disc hypoplasia in both eyes and retinopathy of prematurity, accompanied by retinal hemorrhage in his right eye. Around the age of 24 months, the patient was diagnosed with intermittent exotropia with anisometropia and was prescribed spectacles. (Case 2) A 3-year-old male infant was referred to the ophthalmology clinic to evaluate poor fixation, which was found during rehabilitation therapy for cerebral palsy and developmental delay. Fundus examination showed an increased cup/disc ratio bilaterally. A flash visual evoked potential test indicated a decrease in amplitude in his right eye. Intermittent exotropia of forty prism diopters was observed. DNA microarray CGH and FISH tests performed at another hospital revealed microdeletion of chromosome seven (7q35 microdeletion) and CNTNAP2 gene loss. Conclusions: When genetic anomalies associated with ocular development are identified, it is necessary to detect the ophthalmic abnormalities early and provide the appropriate treatment to allow for the development of normal visual function. KCI Citation Count: 0